The Relationship between the Role of the Teacher and the Behavior of Clean and Healthy Living in the School Environment (Covid-19 Pandemic Period) at MI Azzainiah II Karanganyar Paiton Probolinggo - Hafifah, Vivin Nur; Zaman, Muh Kamaruz; Multazamah, Khalidah (Universitas Nurul Jadid, 2022)
Clean and Healthy Living Behavior (PHBS) in schools. Clean and Healthy Living Behavior (PHBS) in schools is a set of behaviors that are practiced by students, teachers and the school community on the basis of awareness as learning outcomes, so that they are able to independently prevent disease, improve their health, and play an active role in creating a healthy environment. The teacher is a person who is admired and imitated, therefore the role of the teacher is very influential on students, because whatever the teacher does, students will follow him.As for the cause of not maintaining the school environment, namely due to a lack of awareness in maintaining the cleanliness of the school environment, for this reason health education is needed about the importance of clean and healthy living behavior. The aim of the research is to analyze the teacher's role in clean and healthy living behavior in the school environment at MI Azzainiah II Karanganyar Paiton Probolinggo. The research method uses a quantitative correlation approach, and simple regression analysis. The results and discussion include the teacher's role in clean and healthy living behavior. The conclusion is that there is an influence of the teacher's role on clean and healthy living behavior. The results showed that there was a relationship between the teacher's role and clean and healthy living behavior with sig. 0.000 (less than α (0.05)).